2021
DOI: 10.1021/acs.chemmater.1c02844
|View full text |Cite
|
Sign up to set email alerts
|

Nano-assembly of a Chemically Tailored Cas9 Ribonucleoprotein for In Vivo Gene Editing and Cancer Immunotherapy

Abstract: Cancer gene therapy based on the clustered regularly interspaced short palindromic repeat (CRISPR) system has been challenging due to the poor delivery and efficacy in vivo. Herein, we report the development of nanoassembled ribonucleoprotein complexes (NanoRNP), which can efficiently block the PD-L1 immune checkpoint and induce an anti-tumor effect in vivo. We utilize CRISPR-associated protein 9 (Cas9) that is chemically derivatized with a low-molecular weight polymer, which condenses with single-guide RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Direct internalization of Cas9/sgRNA into cells can take place with low efficiency. 12 The editing of bacterial tet, cat, and aph(3′)-Ia implies a possible internalization of Cas9/sgRNA without the assistance of NCDs, albeit with a significantly lower cleavage efficiency (11.9−25.7%). The cleavage of ARGs was further evaluated by qRT-PCR.…”
Section: Targeting Antibiotic-resistant E Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Direct internalization of Cas9/sgRNA into cells can take place with low efficiency. 12 The editing of bacterial tet, cat, and aph(3′)-Ia implies a possible internalization of Cas9/sgRNA without the assistance of NCDs, albeit with a significantly lower cleavage efficiency (11.9−25.7%). The cleavage of ARGs was further evaluated by qRT-PCR.…”
Section: Targeting Antibiotic-resistant E Colimentioning
confidence: 99%
“…The continued widespread use of antibiotics in animal agriculture, as well as intense use of antibiotics and large-scale application of disinfectants during COVID-19 pandemic have accelerated the global spread of antibiotic resistance genes (ARGs) in the environment. To reduce the persistence and related health risks of ARGs, effective strategies are urgently needed to maintain both public and ecosystem health . Current attempts include degradation of extracellular ARGs, reduction of antibiotic-resistant bacteria (ARB), and inhibition of ARG transfer. , Given that levels of antibiotic resistance can be increased through gene amplification, elimination at gene level ( e.g ., genome editing) is necessary to truly minimize ARG propagation. The clustered regularly interspaced short palindromic repeats (CRISPR) system and CRISPR-associated protein 9 (Cas9) have enabled a new era for gene editing. Having the advantages of precise target-positioning, fast gene deletion, ease of customization, and no disturbance on nontarget populations, the CRISPR/Cas system is regarded as a promising strategy for reducing ARGs in a sequence-specific manner …”
Section: Introductionmentioning
confidence: 99%
“…The knockout also resulted in significant infiltration of CD4 + and CD8 + T lymphocytes in the tumour microenvironment indicating significant immune activation. In a similar strategy, PD-L1 was blocked by CRISPR-Cas9 derivatized with a low molecular weight branched poly(ethylene imine) [ 102 ]. The gene editing efficiency was confirmed by observing the down-regulation of PD-L1 and consequent suppression of tumour growth in melanoma bearing mice models.…”
Section: Recent Developments In Cancer Immunotherapymentioning
confidence: 99%
“…Programmable hydrogels have also been reported to improve the cargo loading and overall performance of the polymeric platforms, which is crucial for injectable biomaterials. , Brambilla et al also showed that polymer-based microneedles can be successfully used for individualized diagnostic and monitoring . Further, promising reports toward individualized therapy, however, pertain to using specialized nucleic acids and antibodies as cargo, such as the work of Li et al, Chung et al, and Caruso et al…”
mentioning
confidence: 99%
“…14,15 Brambilla et al also showed that polymer-based microneedles can be successfully used for individualized diagnostic and monitoring. 16 Further, promising reports toward individualized therapy, however, pertain to using specialized nucleic acids and antibodies as cargo, such as the work of Li et al, 17 Chung et al, 18 and Caruso et al 19 It is clear that the road to the "perfect" delivery platform, if that ever exists, is not easy or in this sense straightforward, but we are learning valuable information along the way. This has already made the rapid production of vaccines for SARS-Cov-2 possible, and the next frontier is personalized targeted therapy.…”
mentioning
confidence: 99%